Do Preoperative β-blockers Improve Postoperative Outcomes in Patients Undergoing Cardiac Surgery? Challenging Societal Guidelines. Issue 10 (October 2014) - Toppen, William; Sareh, Sohail; Satou, Nancy; Shemin, Richard; Hunter, Curtis; Buch, Eric; Benharash, Peyman
Preoperative β-blockers (BBs) are widely administered to reduce morbidity and mortality among surgical patients. In fact, the Society of Thoracic Surgeons uses the administration of preoperative BBs as a quality metric. Recent reports, however, have questioned the benefit and safety of pre-operative BB administration. The aim of our study was to investigate whether preoperative BBs lead to improved surgical outcomes in patients undergoing cardiac surgery. A review of our prospectively maintained institutional database was done to identify adults undergoing cardiac operations at our institution from 2008 to 2013. Survival to discharge was the primary outcome with several additional secondary measures of morbidity included. A total of 2120 patients were included in the analysis and a multivariate logistic regression model was developed to adjust for differences between patient groups. After adjustment, BB administration was associated with lower odds of both prolonged ventilation (odds ratio [OR], 0.73; P = 0.032) and prolonged length of stay (OR, 0.79; P = 0.044). BB use was not associated with significant differences in other outcomes such as mortality or postoperative atrial fibrillation. Our study found that preoperative BBs may not be associated with sufficiently improved outcomes to justify their use as a quality metric in this population. Thus, prospective studies are warranted.